Congenital Langerhans Cell Histiocytosis with Placental Involvement. (May 2013) - Terry, Jefferson; Pluchinotta, Francesca R.; Sanders, Stephen P.; Vergilio, Jo-Anne; Hyde, Scott R.; Boyd, Theonia K.
Congenital presentations of Langerhans cell histiocytosis (LCH) are exceedingly rare, and concurrent placental parenchymal involvement has not been definitively documented in the literature. We present 2 cases of congenital multisystem LCH with placental involvement resembling chronic villitis. Placental examination may provide the initial diagnostic evidence of LCH and may significantly influence patient management and outcome; however, the prognostic implications remain unclear. In a clinical context suspicious for congenital LCH, the observation of chronic villitis should prompt consideration of placental involvement by LCH.